Solution;
(D2-3D+2)y=2cos(2x+3)+2ex
Rewrite;
D2y-3Dy+2y=2cos(2x+3)+2ex
y"-3y'+2y=2cos(2x+3)+2ex
The equation can be solved using variation of parameters.
The general solution takes the form ;
y=yc+yp
To solve for yc;
An auxiliary equation can be given as;
m2-3m+2=(m-2)(m-1);
m=2 or m=1
yc=C1e2x+C2ex
To solve yp let yp=yp1+yp2 since g(x) of the equation is a combination.
Solve yp1 from y"-3y'+2y=2cos(2x+3)
Let yp1=Acos(2x+3)+Bsin(2x+3)
"y'_{p1}"=-2Asin(2x+3)+2Bsin(2x+3)
"y''_{p1}" =-4Acos(2x+3)-4Bcos(2x+3)
Replace back in the equation;
-4Acos(2x+3)-4Bsin(2x+3)-3{-2Asin(2x+3)+2Bcos(2x+3)}+2{Acos(2x+3)+Bsin(2x+3)}=2cos(2x+3)
Distribute;
(-4A-6B+2A)cos(2x+3)+(-4B+6A+2B)sin(2x+3)=2cos(2x+3)
This means;
-4A-6B+2A=2
-4B+6A+2B=0
Solve for A and B using both equation;
B=3A
-4A-6×3A+2A=2
-4A-18A+3A=2
A="\\frac{-1}{10}" ,B=-"\\frac{3}{10}"
So that;
yp1="\\frac{-1}{10}" cos(2x+3)-"\\frac{3}{10}" sin(2x+3)
Solve yp2 from y"-3y'+2y=2ex
Let yp2=Axex
"y'_{p2}" =A(ex+xex)ex=A(1+x)ex
"y''_{p2}" =A(2ex+xex)=A(2+x)ex
Substitute in the equation;
A(2+x)ex-3(A(1+x)ex)+2Axex=2ex
Distribute;
(2A+Ax-3A-3Ax+2Ax)ex=2ex
2A-3A=2
A=-2
yp2=-2xex
The general solution of the equation will be;
y=yc+yp
y=C1e2x+C2ex-"\\frac{1}{10}"cos(2x+3)-"\\frac{3}{10}"sin(2x+3) -2xex
Comments
Leave a comment